(3GdebOeI GdLRQjIs - (3GdLRQj, CHh GdNjQ, GHf GdLRQj, TeS GdOjf, eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa (B833(3g`s
(3ChdgG (B:s
(3jbhd QGLj Yah QH SGeY (B,,(3eMeO Hf eMeO GdLRQj GdTGaYj (B,,, (3GdMeO ddg hUdi Gddg (B,, (3Ydi fHjg heUWaGg (B,, (3eMeO hBdg hUMHg (B,,, (3hebQF GdbQBf eY eMHg (B...s
(3BNQgG (B:s
... (3EdG HaJM Ch HfUe hGTe (B,, (3ETGQI HGdVe aj QaY hVe (B,, (3hbO JbVi fXej GdebOeg (B,, (3efj dbGQF GdbQBf JbOeg (B,,, (3hGdMeO ddg dgG GdNJGe (B,, (3Ke GdUdGI hGdSdGe (B,, (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\45s
(3cTa GdXfhf (B2\1799s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs